TRANSFORMASI PENDIDIKAN ISLAM DI JAMBI: DARI MADRASAH KE PESANTREN - Ali Muzakir (Islam Realitas: Journal of Islamic and Social Studies, 2017)
Traditional Islamic education model does not only teach Islam but also provides practical knowledge for modern life. The desire is a great opportunity, because Islamic education in Indonesia has diverse backgrounds, systems, and nomenclature, such as madrassas, boarding schools, rangkang, meunasah, and surau. The model of madrasah education and pesantren seems to be the most viable pedestal. Particularly the pesantren system, rooted in Javanese tradition, is the most widely influenced model of Islamic education in Indonesia. This paper discusses the struggle of madrasah and pesantren in Jambi, with a social-historical approach. The focus of research on some of the most established madrassas in Jambi, which became the forerunner of other madrasah development in Jambi Province. The initial characteristics of Islamic education institutions in Jambi are madrasah. In practice, Madrasahs in Jambi have developed a model of traditional Islamic education, characterized by the study of yellow books, the figures of the master teachers (kyai), students, and boarding schools. The characteristics are similar to the pesantren in Java; minus mosque. In the development, there is a sense of imbalance in responding to changes in the national education system, especially those projected by the Ministry of Religious Affairs. Model pendidikan Islam tradisional tidak hanya mengajarkan Islam tetapi juga membekali ilmu praktis untuk kehidupan modern. Keinginan tersebut menjadi peluang besar, karena pendidikan Islam di Indonesia memiliki latar belakang sejarah, sistem, dan nomenklatur yang beragam, seperti madrasah, pondok pesantren, rangkang, meunasah, dan surau. Model pendidikan madrasah dan pesantren tampaknya menjadi tumpuan yang paling viable. Terutama sistem pesantren, yang berakar pada tradisi Jawa, adalah paling luas mempengaruhi model pendidikan Islam di Indonesia. Tulisan ini membahas pergulatan madrasah dan pesantren di Kota Jambi, dengan pendekatan sejarah-sosial. Fokus penelitian pada beberapa madrasah yang didirikan di Kota Jambi, yang menjadi cikal-bakal pengembangan madrasah lainnya di Provinsi Jambi. Karakteristik awal lembaga pendidikan Islam di Jambi adalah madrasah. Dalam praktiknya, madrasah-madrasah di Jambi mengembangkan model pendidikan Islam tradisional, yang bercirikan kajian kitab kuning, figur tuan guru (kyai), murid, dan pondok. Karakteristik tersebut mirip dengan pesantren di Jawa, tetapi minus masjid. Dalam perkembangannya, terjadi kegamangan dalam merespon perubahan-perubahan dalam sistem pendidikan nasional, khususnya yang diproyeksikan oleh Kementerian Agama.